1969
DOI: 10.1139/y69-108
|View full text |Cite
|
Sign up to set email alerts
|

The role of hemodynamic factors on urinary calcium and magnesium excretion

Abstract: The effects of unilateral vasodilatation and alterations in the mean arterial pressure upon the renal handling of calcium and magnesium were studied by clearance methods in dogs. Unilateral vasodilatation was produced by infusion of acetylcholine or bradykinin into the left renal artery, while arterial pressure was altered by aortic constriction, carotid occlusion and vagotomy, or by systemic infusion of angiotensin. Urinary electrolyte excretion was increased markedly by the infusion of each vasodilator and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1971
1971
1984
1984

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…However, most studies of J, in the proximal tubule in vitro find 50% of this rate, i.e., 0.8-1.0 nl/mm * min (15,18,33,37 The finding of passive calcium transport in the S2 segment of the superficial proximal convoluted tubule of the rabbit is consonant with the published literature that suggests that there is an interdependence of sodium and calcium (38,39). Those maneuvers, which depress proximal tubular reabsorption of sodium and water, such as volume expansion (38), PTH, (40), insulin (41), renal vasodilators (42), and acetazolamide (43), also similarly depress proximal tubular reabsorption of calcium, which results in parallel excretion of sodium and calcium in the final urine. In contrast, those factors which dissociate sodium from calcium in the final urine enhance either distal active sodium reabsorption, such as mineralocorticoids (44, 45), or distal active calcium reabsorption, such as PTH (40) or thiazide diuretics (46).…”
Section: Discussionmentioning
confidence: 67%
“…However, most studies of J, in the proximal tubule in vitro find 50% of this rate, i.e., 0.8-1.0 nl/mm * min (15,18,33,37 The finding of passive calcium transport in the S2 segment of the superficial proximal convoluted tubule of the rabbit is consonant with the published literature that suggests that there is an interdependence of sodium and calcium (38,39). Those maneuvers, which depress proximal tubular reabsorption of sodium and water, such as volume expansion (38), PTH, (40), insulin (41), renal vasodilators (42), and acetazolamide (43), also similarly depress proximal tubular reabsorption of calcium, which results in parallel excretion of sodium and calcium in the final urine. In contrast, those factors which dissociate sodium from calcium in the final urine enhance either distal active sodium reabsorption, such as mineralocorticoids (44, 45), or distal active calcium reabsorption, such as PTH (40) or thiazide diuretics (46).…”
Section: Discussionmentioning
confidence: 67%
“…In the intact state, CCTz/GFR was 2.38±0.17 and after T-PTX, 1 (28) in dogs has been repeatedly confirmed (32)(33)(34)(35)(36).…”
Section: Resultsmentioning
confidence: 76%
“…Usually increments of 10-85% in GFR in the dog induce little change in uri nary calcium and sodium excretion, imply ing a compensatory increase in tubular reab sorption of these ions [22], In contrast, renal vasodilatation with acetylcholine and bradykinin causes parallel increases in sodium and calcium clearances by inhibiting tubular reabsorption of these ions [17], Thus, part of the calcium losses in this study may be asso ciated with the vasodilatation or with the solute diuresis observed with calcium block ers [37]. Finally, a direct effect of calcium blockers on tubular calcium transport seems unlikely since compound D-600, a methoxy derivative of verapamil, has no direct effect when applied to the lumen of the proximal tubule in the rat [16], Potassium excretion and the fractional excretion of potassium were markedly en hanced by the calcium blockers.…”
Section: Discussionmentioning
confidence: 99%